Energy and Economic Analysis of Eucalyptus Plantation for Woodchips Production in Thailand - Warakhom Wongchai (2019)
© 2018 Asian Institute of Technology. This article presents energy and economic analysis of Eucalyptus plantation for woodchips production as energy crop in North Thailand. The selected site was Sahacogen Green Co., Ltd. plantation area covering Lamphun and Lampang province. The investigated data of energy and economy were based on the data from experimental plantation and recorded data from the company, which included seedling, soil preparation and conditioning, cultivation, stump removal and soil recovery, harvesting and transportation. Eucalyptus plantation has been established since 2008 with a 2. 0 × 3. 0 m2 spacing. It was managed as a Short Rotation Coppice (SRC) which was first harvested at the 4th year following by 3 rotations of every 3 years. Stumps were removed, and soil recovery was counted at the end of 13th years. For biomass harvesting, saw cutting machine, tractor and Vermeer BC1000XL were used for woodchips production in the field at the end of each rotation period. Woodchips were transferred by truck to the steam power plant warehouse. The results of evaluation showed that woodchips production was characteristics of a highly efficient energy system with Cumulative Energy Demand (CED) 22.34 MJ/GJ of biomass and Net Energy Ratio (NER) of 44.76. The monetary values refer to cash inflows/outflow accomplished at the end of the cultivation period (2021) when assuming the woodchips price of 31.25 USD/t 40 wt% moisture, discount rate of 5.0% and inflation rate of 0.0% for 13 years on average indicating 1828.40 USD/ha which is equivalent to 2.46 USD/GJ. The economy of woodchips production project in terms of Net Present Values (NPV) and Internal Rates of Return (IRR) was -159.18 USD/ha and 3.94%, respectively.